Co-Supplementation of Diet with Saccharomyces cerevisiae and Thymol: Effects on Growth Performance, Antioxidant and Immunological Responses of Rainbow Trout, Oncorhynchus mykiss - Morteza Yousefi; Hossein Adineh; Ali Taheri Mirghaed; Seyyed Morteza Hoseini (Animals)
This study assessed the effects of thymol and yeast Saccharomyces cerevisiae on the growth performance, antioxidant capacity and immunological responses and gut immunological transcripts in rainbow trout, Oncorhynchus mykiss. Two hundred and seventy fish (6.62 ± 0.18 g) were distributed in 18 aquaria (15 fish per aquarium) as a 2 × 3 factorial design. The fish were fed on diets containing 0 and 1 × 108 cfu/g of yeast and 0, 250 and 500 mg/kg of thymol for 60 days. The results showed that dietary yeast supplementation led to significantly improved fish weight gain and feed efficiency (p < 0.05). Thymol and yeast supplementation affected the hepatic antioxidant status, leading to lower lipid peroxidation and higher glutathione reserves (p < 0.05). Thymol and yeast supplementation led to significantly lowered plasma aspartate aminotransferase levels (p < 0.05). Dietary yeast supplementation led to significantly elevated plasma and mucus lysozyme, plasma alternative complement, immunoglobulin and mucus alkaline phosphatase levels. In contrast, thymol supplementation led to significantly increased plasma lysozyme and mucus alkaline phosphatase levels (p < 0.05), whereas it had no significant effects on other immunological parameters. The mucus bactericidal activities were improved by dietary yeast but both supplements enhanced the plasma bactericidal activity (p < 0.05). Thymol and yeast supplementation significantly up-regulated the expression of tumor necrosis factor-alpha, interleukin-1 beta, transforming growth factor-beta, beta-defensin and heat shock protein-70 in the hindgut (p < 0.05). In conclusion, dietary yeast supplementation was particularly effective in enhancing fish growth performance and non-specific immunity, while thymol supplementation primarily led to improved antioxidant capacity. Notably, a dietary dose of 250 mg/kg of thymol alone failed to affect the gut transcription as much as 500 mg/kg; however, the co-supplementation of 250 mg/kg of thymol and yeast led to comparable results.